2022
DOI: 10.1101/2022.10.06.511170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preprint peer review enhances undergraduate biology students’ disciplinary literacy and sense of belonging in STEM

Abstract: Undergraduate education on science publishing and peer review is limited compared to the focus on experimental research. Since peer review is integral to the scientific process and central to the identity of a scientist, we envision a paradigm shift that makes teaching peer review integral to undergraduate science education, and hypothesize that this may facilitate the development of students' scientific literacy and identity formation. To this end, we developed a curriculum for biology undergraduates to learn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Furthermore, the development of scientific literacy is linked to broader educational goals. (Otto et al, 2022) suggest that undergraduate training in peer review can enhance scientific literacy, scientific identity, and a sense of belonging to science. This approach not only fosters disciplinary literacy but also contributes to students' overall scientific understanding.…”
Section: Figure 1 Results Of Analysis Of Students' Scientific Literac...mentioning
confidence: 99%
“…Furthermore, the development of scientific literacy is linked to broader educational goals. (Otto et al, 2022) suggest that undergraduate training in peer review can enhance scientific literacy, scientific identity, and a sense of belonging to science. This approach not only fosters disciplinary literacy but also contributes to students' overall scientific understanding.…”
Section: Figure 1 Results Of Analysis Of Students' Scientific Literac...mentioning
confidence: 99%
“…Some preprint review platforms (such as PREreview) offer structured templates that can help guide new reviewers [ 28 ]. Preprint review is already being incorporated into undergraduate and graduate courses on scientific publishing [ 29 – 31 ]. Furthermore, by focusing journal clubs on preprints rather than journal publications, participants can move beyond simply discussing a paper that is unlikely to change to producing reviews that will help authors and readers.…”
Section: Methodsmentioning
confidence: 99%
“…However, we view our findings as proof of concept for the feasibility of training undergraduate students in aspects of the preprint review process. Together with other promising examples in biology (Otto et al, 2023), we hope that additional disciplines may take this as inspiration for developing similar pedagogical tools according to their specific needs and requirements.…”
Section: Limitationsmentioning
confidence: 97%
“…In addition, previous initiatives were not explicitly embedded into a structured training programme at the undergraduate level. We know of only one exploratory study that reported on successful inclusion of peer review within an undergraduate biology curriculum for 19 students (Otto et al, 2023). The structure of undergraduate programmes can present considerable challenges for teaching peer review because accredited undergraduate degrees are required to deliver specific modules aligned with their programme structures, leaving limited opportunity to add an additional module focused exclusively on peer reviewing.…”
Section: Engaging Undergraduate Students In Preprint Peer Reviewmentioning
confidence: 99%